A Case study of the Spratlys claim issue and how the top three national newspaper viewed it - Lim, Raquel Marie 1975-; Sandoval, MLia Pristine P.; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
This study gives a topographic description of the Spratly Islands and investigates the international issue of its real ownership. It also looked into the economic and strategic significance which are said to be the main reasons for it being a heated topic of debate among its claimant countries, and how the leading newspapers, The Philippine Daily Inquirer, The Philippine Star and The Manila Bulletin, covered the story. The Historical method was predominantly used in conducting this study. Research data compiled from different sources such as books, journals and records together with interviews from people with significant learning provide the bulk of the subject matter. Content analysis of newspaper clippings on the issue looked into the manner in which the story was played up in three representatives in the print media. One aim of the study was to find out what benefits the islands really has to offer its claimant countries, the Philippine in particular. It also sought to shed light on the controversies and issues surrounding the assertions of each nation in dispute. Findings showed that the local major dailies, the Philippine Daily Inquirer, the Philippine Star and the Manila Bulletin, support the Philippines' stand on the topic yet strove to be objective in delivering facts and offering opinions on sensitive matters such as the Spratly contention. The said newspapers reported both sides if the story and their opinion columnists were able to express their individual points of view about the Spratlys.
Vita.
Thesis (A.B. Journalism)--University of the Philippines Diliman
Keywords: Spratly Islands -- Philippine Daily Inquirer -- Attribution of news; Spratly Islands -- Philippine Star -- Attribution of news; Spratly Islands -- Manila Bulletin -- Attribution of news